Abuso sexual infantil e incesto: a ética da escuta na clínica de Françoise Dolto - Mouammar, Christiane Carrijo Eckhardt [UNESP] (2012)
This paper will discuss some aspects of the problem of child sexual abuse, specifically incest, drawing on psychoanalysis and in particular the psychoanalytic proposed by Françoise Dolto allowing their concepts of castration simboligênica, symbolic function, image and body language unconsciously take incest as the object of study to propose a psychoanalytic clinic devoted to listening to the subject, going beyond the legal concerns of policies on reporting and complaints, but not meddle in them, reflecting on the role of the psychologist and psychoanalyst in the clinic for children of sexual abuse.